2023
DOI: 10.3390/agronomy13041115
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Pair of Pulse-Charged Grounded Metal Nets as an Electrostatic Soil Cover for Eradicating Weed Seedlings

Abstract: An electrostatic technique was developed to generate a simple physical method to eradicate weeds in crop fields. The proposed apparatus consisted of double-expanded metal nets connected to a pulse-charging type negative voltage generator and a grounded line. The two metal nets were arranged in parallel at an interval (6 mm) that caused no arc (spark) discharge between the negatively charged metal net (NC-MN) and the grounded metal net (G-MN). The paired nets were used as a soil cover to zap weed seedlings emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous studies [34,35] have suggested that the spark-exposure treatment effectively kills weed seedlings. Thus, we evaluated the effectiveness of an electric spark produced by the present apparatus.…”
Section: Exposure Of Plant Seedlings To An Arc Discharge-mediated Sparkmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [34,35] have suggested that the spark-exposure treatment effectively kills weed seedlings. Thus, we evaluated the effectiveness of an electric spark produced by the present apparatus.…”
Section: Exposure Of Plant Seedlings To An Arc Discharge-mediated Sparkmentioning
confidence: 99%
“…The arc discharge-exposure method for weed control was originally developed by Wilson and Anderson [23]. The principles of electricity used for weed control are provided in previous studies [34,35], where weeds at the soil-emerging stage were killed by directly exposing young shoots to a high-voltage arc (spark) discharge. Arcing is an electrical phenomenon generated by the movement of a high-voltage-mediated negative charge in the air between opposite electric conductors [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of unintentional human contact with electric fences, it resulted in only temporary discomfort [46]. For safe usage, the pulse-charging type of voltage generator was employed to operate screens for eliminating invasive kudzu vines climbing on a fence [47], weed seedlings emerging in crop fields [48], and adult houseflies emerging from underground pupae [49]. Recently, Matsuda et al [50] integrated a continuous-charging type of voltage generator into an unattended electric weeder and effectively controlled ground weeds in a greenhouse orchard while ensuring safety.…”
Section: Arc Discharge-generating Electric Field Screen For Eliminati...mentioning
confidence: 99%